Analysis of Profitability, Sales Growth, and Determinants of Tax Avoidance in PT Indofood CBP Sukses Makmur Tbk Period 2016-2020 - Dhaniel Hutagalung; Shofwatun Hasna; Haniyah Haniyah; Dewiana Novitasari (Universitas Muhammadiyah Enrekang, 2022)
This study aims to determine the effect of profitability and sales growth on the tax avoidance of PT. Indofood CBP Sukses Makmur Tbk period between 2016-2020. Increased sales make the company earn big profits; therefore, the company will tend to practice tax avoidance. Tax avoidance is a legal activity that is often carried out by companies in an effort to reduce tax payments. The data in this study is secondary data in the form of company financial statements. Profitability is measured by Return On Assets (ROA), which is the ratio between net income after tax and total assets. Sales Growth is measured by the formula for the difference between the current and previous year's sales divided by the previous year's sales. While the assessment of tax avoidance behavior is measured by the Cash Effective Tax Rate (CETR), which is the ratio between cash for taxes and profit before tax. The data processing technique in this study used multiple linear regression with the Ordinary Least Square (OLS) method. The results of the classical assumption test carried out explain that the data is normally distributed, there is no multicollinearity disorder between independent variables, the data is linear data and there is no heteroscedasticity, and there is no autocorrelation between residual values. While the results of multiple linear regression indicate that profitability and sales growth have a significant positive effect on tax avoidance. This is in line with the CETR value which tends to be small, which is close to 0, which means that the tax avoidance that occurs is quite large.